ENGAGED: Educating Nurses about Postoperative Delirium on the Neurosurgical Floor. (16th November 2020) - Deme, Palvasha; Ayala, Gabriela; Chorostecki, Jessica; Serias, Mae; Opute, Amaka; Hall, Kristen; Wingfield, Sarah; Bagley, Carlos A
Abstract: INTRODUCTION: Delirium is a common, preventable postoperative complication in older adults which frequently goes unrecognized. Delirium is associated with multiple adverse outcomes including increased length of stay, falls, pressure ulcers, functional decline, and discharge to nursing facility. METHODS: Nurses on the neurosurgical floor were asked to attend a 45-minute educational session conducted by a geriatric health care provider. Surveys regarding delirium knowledge were administered before and after each session. Three Registered Nurses (RNs) became nurse champions to implement the 4AT and facilitate change in nursing workflow. Patient charts were audited using an EMR Reporting Tool to monitor rates of delirium screening. RESULTS: A greater proportion of nurses (76.07%) answered delirium knowledge questions correctly post-intervention as compared to pre-intervention (67.86%). The chi-square test showed the impact of nursing education was statistically significant ( P = .0167, CI = 0.4763-0.9294). Daily delirium screening rates improved from 0% at baseline to 81.6% in a randomly selected 5-day period 7 weeks post-intervention. CONCLUSION: A delirium initiative utilizing nurse champions can be effective in educating nurses about delirium and initiating delirium screening on a postoperative neurosurgical floor. Further studies are needed to determine if nursing delirium education and improved delirium recognition will lead to improved outcomes for older adults undergoing spine surgery.